APPLYING PROJECT-BASED LEARNING TO REINFORCE THE STUDENTS’ CHARACTER - Astri Komara Putri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
21st -century skills become a concerning matter for all educators due to the challenges that the young generation will face in the future. And educators are on the essential duty to implement the proper teaching methods to support the students in achieving the competencies as well. The presence of